Preparation method of multilayer flexible electromagnetic shielding film

By electrolessly plating nickel and copper on polyethylene terephthalate fiber fabrics and using hot press to enhance the structure, the problem of preparation difficulty and impedance mismatch of traditional metal-based materials was solved, and a high-efficiency electromagnetic shielding performance was prepared Multi-layer flexible electromagnetic shielding film achieves low-cost and efficient electromagnetic wave shielding effect.

CN119239095AActive Publication Date: 2025-01-03HARBIN LIHAI JIAYUAN TECH DEV CO LTD

Patent Information

Application Number
CN202411359835.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

Traditional metal-based electromagnetic shielding materials have problems such as high density, low stability in the air, easy to corrode, difficult to prepare and easy to break. The high filling ratio leads to increased viscosity and reduced fluidity of the material, affecting the continuity and uniformity of the polymer. The problems of mechanical properties and secondary pollution need to be solved urgently.

Method used

Polyethylene terephthalate fiber fabrics are used for electroless nickel and copper plating, and the structure and mechanical properties are enhanced by hot pressing, and the gaps between fiber fabrics are filled with PET to form a multi-layer flexible electromagnetic shielding film to avoid metallic appearance. The layer is oxidized to improve shielding efficiency.

Benefits of technology

The prepared multi-layer flexible electromagnetic shielding film has good mechanical properties, thermal stability, low cost and high-efficiency electromagnetic shielding performance, and can shield >99.99% electromagnetic waves in the 8-12GHz band, breaking through the limitations of traditional metal-based materials. , providing new ideas for the field of electromagnetic shielding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119239095A_ABST
    Figure CN119239095A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multilayer flexible electromagnetic shielding film. The method comprises the following steps: (1) pretreating a polyethylene glycol terephthalate fabric; (2) activating the pretreated PET fabric; (3) preparing a chemical nickel-plating solution and a chemical copper-plating solution, and respectively putting the PET fabric activated in the step (2) into the chemical nickel-plating solution and the chemical copper-plating solution to respectively obtain a PET nickel-plated fiber fabric (PET / Ni) and a PET copper-plated fiber fabric (PET / Cu); (4) respectively washing the PET / Ni and the PET / Cu obtained in the step (3) with deionized water, and drying the PET / Ni and the PET / Cu; and (5) performing hot pressing on PET / Ni and PET / Cu obtained in the step (4), using an aluminum foil as a substrate, arranging an upper stainless steel plate and a lower stainless steel plate, and performing natural cooling to room temperature after hot pressing to obtain the multi-layer flexible electromagnetic shielding film. The material has good mechanical properties and excellent thermal stability, and has the characteristics of simple process and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic shielding composite materials, and in particular relates to a method for preparing a multi-layer flexible electromagnetic shielding film. Background Art

[0002] With the popularization of electronic products, while bringing convenience to people, they also generate high-frequency electromagnetic waves. The electromagnetic (EM) radiation caused by the electrical energy and magnetic energy transferred together in space can affect the functions of electronic products and cause adverse health problems to organisms. Efficient attenuation of electronic radiation is crucial for the booming electronic device fields such as portable electronic products, radio communications, aerospace, etc.

[0003] Traditionally, electromagnetic interference shielding materials have been dominated by metal materials. However, with the continuous development of technology, the demand for lightweight, highly durable and easy-to-form materials is increasing, and metal materials are gradually being replaced by polymer composites. Polymer-based composites as EMI shielding materials also have certain limitations. For example, stainless steel fibers are doped into PP and stainless steel fiber / PP composite foam is prepared by injection foaming process. The introduction of pores reduces the density of the system and improves the electromagnetic shielding efficiency of the system. However, metal fibers have the disadvantages of high density, low stability in air, easy corrosion, difficult preparation and easy breakage, which limits their development.

[0004] High filling ratio and high conductivity can give the material excellent electromagnetic shielding performance, but high filling ratio will increase the viscosity of the material, reduce fluidity and processability, and affect the continuity and uniformity of the polymer. It will also lead to serious impedance mismatch, and its mechanical properties and secondary pollution problems also need to be solved urgently. Summary of the invention

[0005] In order to overcome the above problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a multi-layer flexible electromagnetic shielding film. The multi-layer flexible electromagnetic shielding film prepared by this preparation method has good mechanical properties and excellent thermal stability, and has the characteristics of simple process and low cost.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a multi-layer flexible electromagnetic shielding film comprises the following steps:

[0008] (1) Pretreatment of polyethylene terephthalate (PET) fabric;

[0009] (2) activating the pretreated PET fabric;

[0010] (3) preparing a chemical nickel plating solution and a chemical copper plating solution, and placing the PET fabric activated in step (2) into the chemical nickel plating solution and the chemical copper plating solution, respectively, to obtain a PET nickel-plated fiber fabric (PET / Ni) and a PET copper-plated fiber fabric (PET / Cu), respectively;

[0011] (4) rinsing the PET / Ni and PET / Cu obtained in step (3) with deionized water for 4 to 5 times respectively, and drying;

[0012] (5) Hot pressing the PET / Ni and PET / Cu obtained in step (4), using aluminum foil as a substrate, and setting upper and lower stainless steel plates, from top to bottom, stainless steel plate, aluminum foil, PET / Cu, PET / Ni, aluminum foil, stainless steel plate, and naturally cooling to room temperature after hot pressing to obtain a multi-layer flexible electromagnetic shielding film.

[0013] In the step (1), the PET is cut into 4×4 cm 2 For blocks of different sizes, take 50 mL of anhydrous ethanol, ultrasonicate for 30 to 40 min at room temperature and dry.

[0014] The step (2) is specifically:

[0015] 1. Prepare nickel plating activation solution, m(NiSO 4 6H 2 O):m(NaH 2 PO 2 ·H 2 O):m(H 2 O) = 1.5 ~ 2.0: 2.0 ~ 3.5: 30.0 ~ 45.0, ultrasonic activation at a temperature of 60 ~ 65 ° C for 30 ~ 40 minutes, so that the surface of the PET fabric is uniformly adsorbed with nickel ions;

[0016] 2. Prepare copper plating activation solution, 1-1.5 g / L AgNO 3 , soak at room temperature for 5 to 8 minutes, rinse the surfaces of the two PET fiber fabrics separately with deionized water, and dry them.

[0017] In step (3), 100-200 mL of chemical nickel plating solution is prepared, wherein 25-50 g / L NiSO 4 6H 2 O, 25-50 g / L NaH 2 PO 2 ·H 2 O, 5-10 g / L Na 3 C 6 H 5 O 7 .2H 2 O, 5-10 g / L CH3 COONa, with NH 3 ·H 2 O adjusts pH to 5, and reacts in a water bath at 90-100℃ for 1-2h;

[0018] Prepare 100-200 mL of chemical copper plating solution, including 8-16 g / L CuSO 4 ·5H 2 O, 40~80g / LNaH 2 PO 2 ·H 2 O, 0.9~1.8g / L NiSO 4 6H 2 O, 30-60 g / LH 3 BO 3 , 15-30 g / L trisodium citrate dihydrate, 4-8 mg / L potassium ferrocyanide, 6-12 mg / L 2′2-bipyridine, 12-24 mL / L methanol, react in a water bath at 65-70°C for 2 hours.

[0019] In the step (5), the upper and lower stainless steel plates are heated to 230-240° C. in 60-70 minutes, PET-Cu and PET-Ni are hot pressed, and the procedure is terminated after keeping the temperature for 20-35 minutes.

[0020] Beneficial effects of the present invention:

[0021] The present invention uses polyethylene terephthalate fiber fabric as the substrate, (1) grows a nano metal layer on PET by chemical plating, and adopts hot pressing to enhance the structure and mechanical properties of the shielding fabric. (2) During the hot pressing process, the polymer coated with the metal shell is heated and melted, which can further fill the gaps between the fiber fabrics to isolate the sample from contact with the air and prevent the metal outer layer from being oxidized. Figure 2 The fiber fabric shown in the figure has a uniform surface morphology after hot pressing. Due to the melt filling of PET, the surface of the product also presents a continuous metallic luster, which improves the flatness of the fiber film. A polymer-based electromagnetic shielding composite material is obtained. (3) The shielding composite material prepared by the present invention has low cost, good flexibility, high strength, and is resistant to bending and folding without being easily damaged. At the same time, within the waveband range of 8-12GHz, it can shield >99.99% of electromagnetic waves. (4) The present invention has potential application value in the fields of military industry and various electronic devices. By using this flexible polymer-based composite material and a production-compatible molding process, it has broken through the limitations of traditional metal-based shielding materials to a certain extent, and provided new ideas for the development of the electromagnetic shielding field. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the hot pressing process of the present invention.

[0023] Figure 2 The following are the actual pictures of hot pressing of PET / Ni and PET / Cu single layers and PET / Ni-Cu stacking layers.

[0024] Figure 3 SEM image of chemically plated copper on polyethylene terephthalate fabric.

[0025] Figure 4 This is the total electromagnetic shielding effectiveness curve of the three-layer polymer fiber and metal composite hot-pressed shielding fabric prepared in Example 3.

[0026] Figure 5 This is a graph showing how the absorption and shielding effectiveness of the three-layer polymer fiber and metal composite hot-pressed shielding fabric prepared in Example 3 varies with frequency.

[0027] Figure 6 This is a graph showing how the reflection shielding effectiveness of the three-layer polymer fiber and metal composite hot-pressed shielding fabric prepared in Example 3 varies with frequency.

[0028] Figure 7 This is the total electromagnetic shielding effectiveness curve of two sheets of the polymer fiber and metal composite hot-pressed shielding fabric prepared in Example 2 before hot pressing and after hot pressing. DETAILED DESCRIPTION

[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0030] Example 1

[0031] A method for preparing a multi-layer flexible electromagnetic shielding film comprises the following steps:

[0032] (1) Pre-treat polyethylene terephthalate (PET) fabric and cut PET into 4×4 cm 2 For blocks of different sizes, take 50 mL of anhydrous ethanol, ultrasonicate for 30 min at room temperature and dry.

[0033] (2) Prepare nickel plating activation solution, m(NiSO 4 6H 2 O):m(NaH 2 PO 2 ·H 2 O):m(H 2 O)=1.5:2.0:30.0, ultrasonic activation was carried out for 30 min at a temperature of 60°C to make the surface of the PET fabric evenly adsorb nickel ions; at the same time, a copper plating activation solution was prepared, 1g / L AgNO 3 , the PET fabric was soaked at room temperature for 5 min, the surfaces of the two PET fiber fabrics were rinsed with deionized water respectively, and then dried.

[0034] (3) Electroless nickel and copper were electrolessly plated on the activated PET fabric, respectively, and 100 mL of electroless nickel plating solution was prepared, wherein 25 g / L NiSO 4 6H 2 O, 25 g / L NaH 2 PO 2 ·H 2 O, 5g / L Na 3 C 6 H 5 O 7 .2H 2 O, 5g / L CH 3 COONa, with NH 3 ·H 2 O to adjust pH ≈ 5, react in a 90 ° C water bath for 2 h; prepare 100 mL of chemical copper plating solution, including 8 g / L CuSO 4 ·5H 2 O, 40 g / L NaH 2 PO 2 ·H 2 O, 0.9 g / L NiSO 4 6H 2 O, 30g / LH 3 BO 3 , 15 g / L trisodium citrate dihydrate, 4 mg / L potassium ferrocyanide, 6 mg / L 2′2-bipyridine, 12 mL / L methanol, react in a 65°C water bath for 2 h.

[0035] (4) Rinse PET / Ni and PET / Cu with deionized water for 4 to 5 times respectively and dry them.

[0036] (5) PET / Ni and PET / Cu were hot pressed, using aluminum foil as the substrate, and upper and lower stainless steel plates were set to heat up to 230°C for 60 minutes. The PET / Cu and PET / Ni single layers were hot pressed separately, and the process was terminated after keeping the temperature for 30 minutes, and the plates were naturally cooled to room temperature.

[0037] Figure 2 These are the actual pictures of hot pressing of PET / Ni and PET / Cu single layers and PET / Ni-Cu stacking. It can be seen that the surface of the sample has a uniform metallic luster and has good mechanical strength and flexibility.

[0038] Figure 3Scanning electron microscope image of chemical copper plating on polyethylene terephthalate fabric. The fiber diameter is 17-19 μm. As the substrate for chemical plating, it has a rich specific surface area. In the chemical plating process, materials with a larger specific surface area can usually obtain a more uniform coating because they provide more reaction sites, making it easier for the reducing agent to contact the material surface. In addition, materials with a larger specific surface area usually have better catalytic activity, which can promote the reduction of metal ions in the chemical plating solution into metals to form a uniform coating.

[0039] Example 2

[0040] A method for preparing a multi-layer flexible electromagnetic shielding film comprises the following steps:

[0041] (1) Pre-treat polyethylene terephthalate (PET) fabric and cut PET into 4×4 cm 2 For blocks of different sizes, take 50 mL of anhydrous ethanol, ultrasonicate for 30 min at room temperature and dry.

[0042] (2) Prepare nickel plating activation solution, m(NiSO 4 6H 2 O):m(NaH 2 PO 2 ·H 2 O):m(H 2 O)=1.5:2.0:30.0, ultrasonic activation was carried out for 35 min at a temperature of 60°C to make the surface of the PET fabric evenly adsorb nickel ions; at the same time, a copper plating activation solution was prepared, 1g / L AgNO 3 , the PET fabric was soaked at room temperature for 5 min, the surfaces of the two PET fiber fabrics were rinsed with deionized water respectively, and then dried.

[0043] (3) Electroless nickel and copper were electrolessly plated on the activated PET fabric, respectively, and 100 mL of electroless nickel plating solution was prepared, wherein 25 g / L NiSO 4 6H 2 O, 25 g / L NaH 2 PO 2 ·H 2 O, 5g / L Na 3 C 6 H 5 O 7 .2H 2 O, 5g / L CH 3 COONa, with NH 3 ·H 2 O to adjust pH ≈ 5, react in a 90 ° C water bath for 2 h; prepare 100 mL of chemical copper plating solution, including 8 g / L CuSO 4 ·5H2 O, 40 g / L NaH 2 PO 2 ·H 2 O, 0.9 g / L NiSO 4 6H 2 O, 30g / LH 3 BO 3 , 15 g / L trisodium citrate dihydrate, 4 mg / L potassium ferrocyanide, 6 mg / L 2′2-bipyridine, 12 mL / L methanol, react in a 65°C water bath for 2 h.

[0044] (4) Rinse PET / Ni and PET / Cu with deionized water for 4 to 5 times respectively and dry them.

[0045] (5) PET / Ni and PET / Cu were hot pressed, using aluminum foil as the substrate, setting the upper and lower stainless steel plates to heat up to 230°C for 60 minutes, stacking PET / Cu and PET / Ni and hot pressing them, and ending the process after keeping the temperature for 30 minutes, and naturally cooling to room temperature.

[0046] Figure 7 is the total electromagnetic shielding effectiveness SE of PET / Ni and PET / Cu shielding fabrics before and after hot pressing T From the curve, we can see that after hot pressing at 230°C, the shielding property of the sample in the X-band range has been greatly improved. This is due to the fact that the molten polymer bonds the two layers of shielding fabric together, which improves the density of the material, reduces internal pores and defects, and helps to reduce the penetration of electromagnetic waves.

[0047] Example 3

[0048] A method for preparing a multi-layer flexible electromagnetic shielding film comprises the following steps:

[0049] (1) Pre-treat polyethylene terephthalate (PET) fabric and cut PET into 4×4 cm 2 For blocks of different sizes, take 50 mL of anhydrous ethanol, ultrasonicate for 30 min at room temperature and dry.

[0050] (2) Prepare nickel plating activation solution, m(NiSO 4 6H 2 O):m(NaH 2 PO 2 ·H 2 O):m(H 2 O)=1.5:2.0:30.0, ultrasonic activation was performed at 60°C for 40 min to make the surface of PET fabric evenly adsorb nickel ions; at the same time, copper plating activation solution was prepared, 1g / L AgNO 3, the PET fabric was soaked at room temperature for 5 min, the surfaces of the two PET fiber fabrics were rinsed with deionized water respectively, and then dried.

[0051] (3) Electroless nickel and copper were electrolessly plated on the activated PET fabric, respectively, and 100 mL of electroless nickel plating solution was prepared, wherein 25 g / L NiSO 4 6H 2 O, 25 g / L NaH 2 PO 2 ·H 2 O, 5g / L Na 3 C 6 H 5 O 7 .2H 2 O, 5g / L CH 3 COONa, with NH 3 ·H 2 O to adjust pH ≈ 5, react in a 90 ° C water bath for 2 h; prepare 100 mL of chemical copper plating solution, including 8 g / L CuSO 4 ·5H 2 O, 40 g / L NaH 2 PO 2 ·H 2 O, 0.9 g / L NiSO 4 6H 2 O, 30g / LH 3 BO 3 , 15 g / L trisodium citrate dihydrate, 4 mg / L potassium ferrocyanide, 6 mg / L 2′2-bipyridine, 12 mL / L methanol, react in a 65°C water bath for 2 h.

[0052] (4) Rinse PET / Ni and PET / Cu with deionized water for 4 to 5 times respectively and dry them.

[0053] (5) PET / Ni and PET / Cu were hot pressed, using aluminum foil as the substrate, setting the upper and lower stainless steel plates to heat up to 230°C for 60 minutes, and hot pressing PET / Cu and two PET / Ni three-layer stacks (PET / Ni-Cu-Ni). The program was terminated after keeping the temperature for 30 minutes and naturally cooled to room temperature.

[0054] Example 4

[0055] A method for preparing a multi-layer flexible electromagnetic shielding film comprises the following steps:

[0056] (1) Pre-treat polyethylene terephthalate (PET) fabric and cut PET into 4×4 cm 2 For blocks of different sizes, take 50 mL of anhydrous ethanol, ultrasonicate for 30 min at room temperature and dry.

[0057] (2) Prepare nickel plating activation solution, m(NiSO 4 6H 2 O):m(NaH 2 PO 2 ·H 2 O):m(H 2 O)=1.5:2.0:30.0, ultrasonic activation was performed at 60°C for 45 min to make the surface of PET fabric evenly adsorb nickel ions; at the same time, copper plating activation solution was prepared, 1g / L AgNO 3 , the PET fabric was soaked at room temperature for 5 min, the surfaces of the two PET fiber fabrics were rinsed with deionized water respectively, and then dried.

[0058] (3) Electroless nickel and copper were electrolessly plated on the activated PET fabric, respectively, and 100 mL of electroless nickel plating solution was prepared, wherein 25 g / L NiSO 4 6H 2 O, 25 g / L NaH 2 PO 2 ·H 2 O, 5g / L Na 3 C 6 H 5 O 7 .2H 2 O, 5g / L CH 3 COONa, with NH 3 ·H 2 O to adjust pH ≈ 5, react in a 90 ° C water bath for 2 h; prepare 100 mL of chemical copper plating solution, including 8 g / L CuSO 4 ·5H 2 O, 40 g / L NaH 2 PO 2 ·H 2 O, 0.9 g / L NiSO 4 6H 2 O, 30g / LH 3 BO 3 , 15 g / L trisodium citrate dihydrate, 4 mg / L potassium ferrocyanide, 6 mg / L 2′2-bipyridine, 12 mL / L methanol, react in a 65°C water bath for 2 h.

[0059] (4) Rinse PET / Ni and PET / Cu with deionized water for 4 to 5 times respectively and dry them.

[0060] (5) PET / Ni and PET / Cu were hot pressed, using aluminum foil as the substrate, setting the upper and lower stainless steel plates to heat up to 230°C for 60 minutes, and hot pressing two layers of PET / Cu and PET / Ni (PET / Cu-Ni-Cu). The program was terminated after keeping the temperature for 30 minutes and naturally cooled to room temperature. Figure 1 It is a schematic diagram of the hot pressing device. During hot pressing, two stainless steel plates of the same thickness are covered with aluminum foil respectively, and then the shielding material is placed in the center of the plate to ensure that the material is heated evenly.

[0061] Figure 4 is the total shielding effectiveness SE of the PET / Ni-Cu-Ni three-layer hot-pressed sample T The shielding efficiency in the range of 8.5 to 9.5 GHz can reach over 99.99999%, and the average shielding effectiveness in the entire X-band range is >60 dB.

[0062] Figure 5 is the absorption shielding effectiveness SE of the PET / Ni-Cu-Ni three-layer hot-pressed sample A The maximum shielding effectiveness in the 8.5-9.5 GHz band reaches about 80 dB, and the average shielding effectiveness in the entire X-band range is > 40 dB.

[0063] Figure 6 is the reflection shielding effectiveness SE of the PET / Ni-Cu-Ni three-layer hot-pressed sample R , the maximum shielding effectiveness in the 9.5-10.5GHz band reaches about 30dB, and the average shielding effectiveness in the entire X-band range is >15dB. Figure 4 , 5 , 6 It can be concluded that the shielding mechanism of the multilayer electromagnetic shielding composite film prepared by the present invention is mainly absorption shielding, which works synergistically with reflection shielding to absorb electromagnetic waves.

[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a multi-layer flexible electromagnetic shielding film, characterized in that: The steps include: (1) Pretreatment of polyethylene terephthalate (PET) fabric; (2) activating the pretreated PET fabric; (3) preparing a chemical nickel plating solution and a chemical copper plating solution, and placing the PET fabric activated in step (2) into the chemical nickel plating solution and the chemical copper plating solution, respectively, to obtain a PET nickel-plated fiber fabric (PET / Ni) and a PET copper-plated fiber fabric (PET / Cu), respectively; (4) rinsing the PET / Ni and PET / Cu obtained in step (3) with deionized water for 4 to 5 times respectively, and drying; (5) Hot pressing the PET / Ni and PET / Cu obtained in step (4), using aluminum foil as a substrate, and setting upper and lower stainless steel plates, from top to bottom, stainless steel plate, aluminum foil, PET / Cu, PET / Ni, aluminum foil, stainless steel plate, and naturally cooling to room temperature after hot pressing to obtain a multi-layer flexible electromagnetic shielding film.

2. The method for preparing a multi-layer flexible electromagnetic shielding film according to claim 1, characterized in that: In the step (1), the PET is cut into 4×4 cm 2 For blocks of different sizes, take 50 mL of anhydrous ethanol, ultrasonicate for 30 to 40 min at room temperature and dry.

3. The method for preparing a multi-layer flexible electromagnetic shielding film according to claim 1, characterized in that: The step (2) is specifically:

1. Prepare nickel plating activation solution, m(NiSO4·6H2O):m(NaH2PO2·H2O):m(H2O)=1.5~2.0:2.0~3.5:30.0~45.0, and perform ultrasonic activation for 30~40min at a temperature of 60~65℃ to make the surface of PET fabric evenly adsorb nickel ions; 2. Prepare copper plating activation solution, 1-1.5 g / L AgNO3, soak at room temperature for 5-8 min, rinse the surfaces of the two PET fiber fabrics with deionized water respectively, and dry them.

4. The method for preparing a multi-layer flexible electromagnetic shielding film according to claim 1, characterized in that: In the step (3), 100-200 mL of chemical nickel plating solution is prepared, wherein 25-50 g / L NiSO4·6H2O, 25-50 g / L NaH2PO2·H2O, 5-10 g / L Na3C6H5O7.2H2O, and 5-10 g / L CH3COONa are contained, NH3·H2O is used to adjust the pH value to 5, and the solution is reacted in a water bath at 90-100° C. for 1-2 hours; Prepare 100-200 mL of chemical copper plating solution, including 8-16 g / L CuSO4·5H2O, 40-80 g / L NaH2PO2·H2O, 0.9-1.8 g / L NiSO4·6H2O, 30-60 g / L H3BO3, 15-30 g / L trisodium citrate dihydrate, 4-8 mg / L potassium ferrocyanide, 6-12 mg / L 2′2-bipyridine, and 12-24 mL / L methanol, and react in a 65-70°C water bath for 2 h.

5. The method for preparing a multi-layer flexible electromagnetic shielding film according to claim 1, characterized in that: In the step (5), the upper and lower stainless steel plates are heated to 230-240° C. in 60-70 minutes, PET-Cu and PET-Ni are hot pressed, and the procedure is terminated after keeping the temperature for 20-35 minutes.

Citation Information

Patent Citations

  • Preparation method of electromagnetic shielding textile

    CN103061114A

  • Nickel coating carbon fiber composite material and preparation method thereof

    CN103724930A

  • Method for preparing aramid composite conductive fibers with nickel / copper coatings

    CN104928914A

  • Two-time hot pressing multiscale ultrathin high performance electromagnetic shielding film and preparation method thereof

    CN110228237A

  • Preparation method and application of hot-pressing enhanced binder-free multifunctional nano-silver fabric

    CN115852680A

Cited By

  • One-step pretreatment activating solution and pretreatment method before chemical copper plating of PET (Polyethylene Terephthalate) fiber

    CN119913491A

  • Preparation method of low-reflection degradable electromagnetic shielding multilayer composite film

    CN121200532A